Motivation and obstacles for weight management among young women - a qualitative study with a public health focus - the Tromsø study: Fit Futures - Anne-Sofie Sand; Nina Emaus; Olaug S. Lian (BMC, 2017)
Abstract Background Due to a worldwide increase in overweight and obesity, weight-management through lifestyle changes has become an important public health issue. Adolescents and young adults comprise a vulnerable group. The transition into adulthood represents a stage in life when establishing good lifestyle habits for the future is important. The aim of this study was to explore motivation and obstacles for weight reduction, weight maintenance and healthy lifestyle choices in young women. Methods We conducted semi-structured in depth interviews with 12 young women, both overweight and normal weight, recruited from a school-based population survey. By the use of thematic analysis we searched the interview text for relevant meaning units that emerged as topics that illuminated our research questions. Results A strong motivation for obtaining or keeping normal weight was clearly present among the participants. Independent of weight-group, the participants described increased levels of physical activity, better eating habits and regularity in daily life as desirable changes. Parents were described as important influencers regarding lifestyle habits. Several participants expressed a need for more information about healthy nutrition and eating. Their motivation for physical activity depended on a positive social setting and elements of joy. The participants described the transition into adulthood including moving out of their parents' home and other structural changes in everyday life, as challenging. It affected their food choices and eating habits and other lifestyle issues. High costs of healthy food and sports activities were frequently mentioned among the obstacles they encountered. Conclusion The results revealed an obvious motivation for lifestyle changes in individuals and environmental challenges for young women in the relevant stage of their life-course. There seems to be a need for health strategies that strengthens individuals' capacity to overcome the environmental challenges in the transition to adulthood. This should include reliable and accessible health education/information regarding healthy nutrition, eating habits, food choices and preparation of meals. Structural initiatives such as easier access to affordable healthy food and less expensive opportunities for physical activity and sports should be considered.